Anti-SARS-CoV-2 vaccination in people with multiple sclerosis: Lessons learnt a year in - Pugliatti, Maura; Hartung, Hans-Peter; Oreja-Guevara, Celia; Pozzilli, Carlo; Airas, Laura; Alkhawajah, Mona; Grigoriadis, Nikolaos; Magyari, Melinda; Van Wijmeersch, Bart; Zakaria, Magd; Linker, Ralf; Chan, Andrew; et al. (Frontiers in Immunology, 2022)
It has been over a year since people with multiple sclerosis (pwMS) have been receiving vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). With a negligible number of cases in which vaccination led to a relapse or new onset MS, experts around the world agree that the potential consequences of COVID-19 in pwMS by far outweigh the risks of vaccination. This article reviews the currently available types of anti-SARS-CoV-2 vaccines and the immune responses they elicit in pwMS treated with different DMTs. Findings to date highlight the importance of vaccine timing in relation to DMT dosing to maximize protection, and of encouraging pwMS to get booster doses when offered.